COVID-19 PANDEMIC IN BRAZIL: NO COMPLIANCE OF POLICIES AND AGGRAVATING ELEMENTS FOR VULNERABLE POPULATION AND ECOSYSTEMS - Silva, Fabio Leandro da; Micheleti, Allan do Amaral; Fushita, Ângela Terumi; Cunha-Santino, Marcela Bianchessi da; Bianchini Jr, Irineu (Interfaces Científicas - Saúde e Ambiente, 2020)
We aim to stand out aggravating factors that can compromise the COVID-19 pandemic in Brazil and the eventual risks for vulnerable people and ecosystems, as well as, suggest future actions that need to be adopted. A theoretical reflection was conducted, considering references available on Scopus and PubMed. Brazilian public policies, adverse effects of COVID-19 pandemic, and future actions were highlighted. We demonstrated that proper water, sanitation, and hygiene (WaSH) are essential to face the pandemic, however, more than 39 million of Brazilians do not have access to basic sanitation and clean drinking-water. There is a possibility of the novel coronavirus be transmitted by untreated wastewater, being necessary to promote actions that improve sanitation, reduce ecosystems threat, and poverty.